Ethnomathematics Approach of Learning Mathematics among the Upper Primary Level Students of West Bengal A Case Study - Halder, Sumanta; Gangmei, Elizabeth (JOURNAL OF INDIAN EDUCATION, 2022)
Ethnomathematics, as a line of study and research of mathematics education, investigates the roots of mathematical ideas and practices that exist within different cultural groups. The aim of the study is to identify the ethnomathematics approach used by students and teachers for learning mathematics at upper primary level. A Descriptive Survey method was adopted for the study. Sample teachers and students were selected randomly from the upper primary schools of North 24 PGS district of West Bengal. Interview and classroom observation schedule was used for data collection. The study found that teachers motivate students to use cultural games and artefacts which promote mathematical knowledge and belief. The majority of students have learned their elementary arithmetic operations like addition, subtraction and basic geometrical concepts using local culture specific methods, artefacts and games like Kathi Khela and Sholo Guti (Sixteen Soldiers).